Joint formation and fracture characteristics of laser welded CFRP/TC4 joints. (September 2019) - Tao, Wang; Su, Xuan; Chen, Yanbin; Tian, Ze
Abstract: Laser welding was employed to join short carbon fiber reinforced polyphenylene sulfide (SCF/PPS) and TC4 alloy inexpensively and quickly. An excellent joint with a large interfacial bonding area was achieved, while the TC4 and the SCF/PPS were tightly joined under the sufficient temperature and pressure. The bubble defects formed easily at the joining interface due to the voids in the PPS resin, SCF/PPS volume shrinkage during the solidification stage, and the decomposition of the PPS resin, and these phenomena were significantly reduced by regulating and controlling welding parameters. As the laser power increased, the tensile shear load first increased and then decreased, which was attributed to the effects of the joining area, bubble defects and PPS decomposition. The maximum tensile shear load of 2052 N was achieved at the optimum laser power of 700 W due to the large interfacial joining area and absence of obvious decomposition. The joint fracture presented mixed fracture characteristics of cohesion and adhesion failures.